High-technology trade: does it enhance national competitiveness? - Idris, Zera Zuryana; Ismail, Normaz Wana; Ibrahim, Saifuzzaman; Hamzah, Hanny Zurina (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to explore the impact of technological development through international trade activities on national competitiveness. As such, the objective of this paper is to empirically examine the impact of engaging in high-tech trade, both exports and imports, on national competitiveness. The research was carried out on a sample of 20 major high-tech exporting countries, over the period 2007 to 2016. An econometric analysis of panel data was employed. Considering the Global Competitiveness Index as the dependent variable, the results indicate that both high-tech exports and imports positively affect national competitiveness. Specifically, the exports of high-tech force technological development and improve national competitiveness. The imports of high-tech act as a mechanism for technology transfer and positively influence national= competitiveness. The findings imply that it will be beneficial for a country to identify and develop potential high-tech industries in order to achieve a higher level of national competitiveness.